Investigating Histological Changes and Gene Expression of Interleukin-8, Interleukin-12, and Interferon Beta in Liver Tissue After Consumption of Lactobacillus rhamnosus GG Probiotic in Steatosis Model Rats - F Rostamkhani (Armaghane Danesh Bimonthly Journal, 2022)
Background & aim: Probiotic consumption can regulate the homeostasis of the digestive system and control metabolic diseases related to the digestive system. Therefore, the purpose of the present study was to determine and investigate histological changes and gene expression of interleukin 12, 8 and interferon beta in liver tissue after 5 weeks of consumption of Lactobacillus rhamnosus GG probiotic in steatosis model rats.